Hegemonic practices in multistakeholder Internet governance: Participatory evangelism, quiet politics, and glorification of status quo at ICANN meetings - Palladino, Nicola (My University, 2023)
In this exploratory study we examine a less scrutinized aspect of multistakeholder arrangements: the presence and directionality of hegemonic power in the language used in the stakeholder deliberations. Specifically, we examine the deliberations of ten stakeholder groups of ICANN’s policy development body. Using meeting transcripts from 2011 to 2020, we operationalized hegemony as a latent, dependent variable (HEIN) by linking stakeholder participation to the policymaking agenda. We employed a mixed-methods approach comprising textual linguistic analysis (using DICTION 7.1), principal components analysis, and an autoregressive moving average model to identify the statistical significance of key variables that emerged from textual linguistic and principal components analyses. We found that three primary rhetorical devices – participatory evangelism, quiet politics, and glorification of the status quo – were present, which reinforce the entrenched power structure that favors some stakeholders and interfere with other stakeholders’ efforts to influence Internet governance decisions. In addition, four Diction variables, Commonality, Leveling Terms, Satisfaction, and Commonality at the GNSO (Generic Names Supporting Organization) level, yielded a positive impact on the production of hegemony, and Insistence was negatively associated with HEIN.
PUBLISHED
Keywords: Deliberations; DIcTIon 7.1; Hegemony; Internet governance; Multistakeholderism